Evidence-based Practice in Pediatric Appendicitis - Ekkarat, Patomphon; Sangkhathat, Surasak (The Thai Journal of Surgery, 2015)
Management of acute appendicitis is one of the most challenging topics in pediatric surgery. Recent researches have focused on systematic approaches in diagnosis and minimally invasive surgical techniques. In order to avoid morbidity caused by delayed management, clinical scoring systems and imaging modalities have been undergoing continuing modifications with an attempt to find the optimal diagnostic algorithm. Although an appendectomy is the mainstay treatment, some recent studies have reported successes with initial non-operative management in selected cases of uncomplicated appendicitis. In cases with an appendiceal mass, evidences have suggested that conservative management is preferable in the pediatric age group. Interval appendectomy for a subsided appendiceal mass is no longer mandatory. As minimally invasive surgery has gained its popularity among pediatric surgeons, laparoscopic appendectomy is an attractive procedure with proven advantage in enhancing recovery and reducing post-operative wound complications, especially in complicated appendicitis.